Collaboration technologies and social computing : 26th International Conference, CollabTech 2020, Tartu, Estonia, September 8-11, 2020, Proceedings /: 26th International Conference, CollabTech 2020, Tartu, Estonia, September 8-11, 2020, Proceedings. ([2020]) - Unknown
No abstract available